MEDIA MASSA DAN PENYEBARAN ISU PEREMPUAN - Machya Astuti Dewi (Jurnal Ilmu Komunikasi, 2009)
Mass media has significant role in dispersing women issues. Especially in conducive political opportunity structure, feminist ideology shared by woman activists grows rapidly. International women discourses informed by mass media influence, adopted, and motivate what women activists will do. And finally mass media play important role in the struggle for gender equality. Mass media inform and campaign for news and informations so that the readers or audiences give greater attention and awareness in women’s rights. In the Indonesia context, many women from Non Govermental Organizations influenced by international issues and international phenomena in their struggle for women empowerment. They learn almost all the international issues and phenomena from mass media, especially newspaper and internet. For the example, the vagina monolog performance in Madisson square motivated the Indonesian women activist to performed the same thing in Indonesia. On the other hand, Indonesian women activists always share their feminist ideologi or campaign for women empowerment in newspapers, magazines and internet. Many Indonesian people realize that the encouregement for women, gender equality and women empowerment are the important things to do. And all what Indonesian women activists have done become a reality that mass media has very important role in campaingn for women issues and gender equality.